1996
DOI: 10.1073/pnas.93.22.12315
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of an arylalkylamine N-acetyltransferase (aaNAT1) from Drosophila melanogaster expressed in the nervous system and the gut.

Abstract: In insects, neurotransmitter catabolism, melatonin precursor formation, and sclerotization involve arylalkylamine N-acetyltransferase (aaNAT, EC 2.3.1.87) activity. It is not known if one or multiple aaNAT enzymes are responsible for these activities. We recently have purified an aaNAT from Drosophila melanogaster. Here, we report the cloning of the corresponding aaNAT cDNA (aaNAT1) that upon COS cell expression acetylates dopamine, tryptamine, and the immediate melatonin precursor serotonin. aaNAT1 represents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 38 publications
0
67
0
1
Order By: Relevance
“…Teleost fish have up to three paralogs (18), and amphioxus has seven aaNAT homolog genes (19). Insects do not have mammalian aaNAT homologs, based on sequence similarity searches of sequenced genomes and phylogenetic analysis (18,19); however, insects do have multiple aaNAT enzymes that show very low sequence identity with mammalian aaNATs (2,7,12). The identified insect aaNAT sequences and the available genome sequences for a number of insect species make it possible to predict hypothetical aaNAT sequences in insects via a bioinformatics approach.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Teleost fish have up to three paralogs (18), and amphioxus has seven aaNAT homolog genes (19). Insects do not have mammalian aaNAT homologs, based on sequence similarity searches of sequenced genomes and phylogenetic analysis (18,19); however, insects do have multiple aaNAT enzymes that show very low sequence identity with mammalian aaNATs (2,7,12). The identified insect aaNAT sequences and the available genome sequences for a number of insect species make it possible to predict hypothetical aaNAT sequences in insects via a bioinformatics approach.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike mammals, insects have evolved multiple aaNATs (2,7,12). In the yellow fever mosquito, Aedes aegypti, 13 putative aaNATs have been identified by a BLAST search using a positively verified Drosophila melanogaster aaNAT sequence; two of these aaNATs have been biochemically identified as aaNAT1 and aaNAT2 (2).…”
mentioning
confidence: 99%
“…These D. melanogaster genes have no homolog in fungi or vertebrates based on sequence analysis, although putative orthologs can be identified in C. elegans (data not shown). The D. melanogaster enzymes acetylate dopamine as a preferred substrate (31,32).…”
Section: Table Vmentioning
confidence: 99%
“…For convenience, they are named C1 to C13 based on their position. Detailed information for these 13 genes is given in Table S2 represents a novel gene family that is unrelated to known acetyltransferases, except for two weakly conserved amino acid motifs (Hintermann et al, 1996). Our phylogenetic analysis, based on amino acid sequences of AANAT, showed that the Chinese tussah moth (Antheraea pernyi) enzyme exhibits the highest degree of homology with the silkworm enzyme.…”
Section: Research Articlementioning
confidence: 97%